Designing educational materials for teaching baseball batting techniques to fifth-grade students in Klender Village - La Ode Maulana Khalifah Khair; Taufik Rihatno; Masti Juniarto (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The objective of this study is to design educational materials for teaching baseball hitting to fifth-grade students at Klender Village Elementary School. This learning model can serve as a valuable resource for teachers in creating instructional materials for teaching baseball hitting to fifth-grade pupils at Klender Village Elementary School. The developed learning model offers diverse and inventive learning opportunities accessible to all students, fostering innovation within the learning process. Materials and methods. The methodology employed in this work is the research and development approach. The objective of this study is to design educational materials for teaching baseball hitting to fifth-grade students at Klender Village Elementary School. The study involved the creation of learning materials for baseball hitting using 5 learning models. These models were then analyzed through the completion of questionnaires by a sample of 15 fifth-grade students and validated by a sports teacher and two expert lecturers. Results. A learning media for baseball hitting was developed, deemed viable, and subsequently assessed for its attractiveness and ease of use. It was found to be suitable for the learning process of baseball hitting. Conclusion. The utilization of media development in baseball games for fifth grade pupils at Klender 10 Pagi Elementary School enhances the effectiveness of learning implementation.